2019
DOI: 10.1007/s00122-019-03410-4
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting genetic loci affecting grain morphological traits to improve grain weight via nested association mapping

Abstract: Key messageThe quantitative trait loci (QTLs) for grain morphological traits were identified via nested association mapping and validated in a natural wheat population via haplotype analysis.AbstractGrain weight, one of the three most important components of crop yield, is largely determined by grain morphological traits. Dissecting the genetic bases of grain morphology could facilitate the improvement of grain weight and yield production. In this study, four wheat recombinant inbred line populations construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…To date, a large number of QTLs for TKW and kernel morphological traits have been mapped in common wheat [ 45 , 48 ]. To investigate whether there were overlapping QTLs in different genetic backgrounds, we compared the QTLs interval in this study with those in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a large number of QTLs for TKW and kernel morphological traits have been mapped in common wheat [ 45 , 48 ]. To investigate whether there were overlapping QTLs in different genetic backgrounds, we compared the QTLs interval in this study with those in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, stable stripe rust resistant germplasms were found among 213 Chinese endemic wheat accessions, and novel adult plant resistance loci for breeding and improvement of durable resistance in wheat were identified. Recent studies have indicated that the Chinese endemic wheat represents unique genetic resources with the potential to contribute novel alleles for broadening the current germplasm gene pools of breeding programs (Gu et al, 2015;Wang et al, 2019). However, a major disadvantage of Chinese endemic wheat is that they inevitably harbor genes that negatively impact agronomic traits, such as a brittle rachis, tough glume, and late maturation.…”
Section: Utilization Of Chinese Endemic Wheat In Resistance Breedingmentioning
confidence: 99%
“…Of which, a total of 201 QTLs were identified for TKW on all chromosomes of durum wheat (Arriagada et al, 2020). In addition, different QTLs for TKW were recently detected on chromosomes 2A, 3B, 4A, 5A, 6A and 7B (Guan et al, 2018;Su et al, 2018;Zhai et al, 2018;Golan et al, 2019;Guan et al, 2019;Sakuma et al, 2019;Wang et al, 2019;Arriagada et al, 2020;Fatiukha et al, 2020;Liu et al, 2020;Mir et al, 2021). The association between different SSR markers and TKW as an indicator for heat tolerance has been also reported in wheat (Ramya et al, 2010;Wang et al, 2012;El-Rawy, 2015;Amallah et al, 2016).…”
Section: Bulked-segregant Analysis (Bsa)mentioning
confidence: 99%